Green design : volume 2 - Lucas, Dorian (S.l. : Braun, 2013)
Green Design, Vol. 2 shows the most varied strategies of environmentally compatible design. Especially notable is the recycling of unusual materials, fair production and fair trade, low-emission use and finally the principal of conversion instead of disposal.
boek